Ginger (Zingiber officinale) A review of varied health benefit - Machowiak, Anna; Ufnalska, Barbara; Fabijański , Artur; Konarska, Anna; Lisiecka, Justyna; Janik, Mateusz; Nowak, Michał; Rychlewska-Duda , Joanna; Firlej, Wojciech; Dukacz, Adrianna (Journal of Education, Health and Sport, 2025)
Introduction: Ginger (Zingiber officinale) is widely valued around the world for its medicinal and culinary properties. Ginger has been used for thousands of years in Traditional Chinese Medicine as a potent curative plant, underscoring its remarkable potential in the realms of nutrition, cuisine and healthcare. A variety of biologically active compounds have been isolated from ginger, including volatile oil, gingerol analogues, diarylheptanoids, phenyl alkaloids, sulfonates, and others. [1] These compounds are known to provide numerous health benefits, such as antioxidant, anti-inflammatory, antimicrobial, or even anti-cancer effects. In addition, accumulating studies have demonstrated that ginger possesses the potential to prevent and manage several diseases, such as neurodegenerative diseases [7], cardiovascular diseases [8], obesity [9], diabetes mellitus [10], chemotherapy-induced nausea and emesis [11], respiratory disorders [12], and pregnancy-related nausea [2]. Aim of the Study: The aim of the study is to present the current state of knowledge of ginger, the effects of ginger consumption on health and examples of its use in medical practice. Materials and methods: The study was constructed by selecting scientific and medical literature utilizing available databases such as PubMed, Google Scholar, Cochrane Library. Based on searching like: ginger, Zingiber officinale; antioxidant; anti-inflammatory; pregnancy-related nausea; chemotherapy-induced vomiting; Conclusion Ginger is an herbal, easily available, low price medication which is associated with low risk and can be substituted for a chemical, scarce and expensive drug. Has a lot of promise in the broad treatment of certain ailments.